Educational Implications of Indigenous Knowledge for Sustainable Development (Bhartiya Knowledge Systems, 2024)
________________________________________________________________________________________Abstract: Indigenous Knowledge Systems (IKS) comprise the lasting traditions, practices, and wisdom of indigenous cultures, intricately linked to their harmonious interaction with the environment. These systems provide sustainable answers to global concerns via creative methodologies in agriculture, resource management, healthcare, and cultural preservation. Incorporating this information into formal education, especially within vocational and environmental courses, has significant potential to enhance ecological equilibrium and cultural resilience. The indigenous practices including conservation methods, herbal remedies, artistic expressions and cultural practices that foster sustainability oriented perspectives. Moreover, these practices offer significant insights into biodiversity protection, natural resource management, and sustainable living practices, in accordance with global development aspiration. This paper aims to highlight the importance of acknowledging and safeguarding indigenous knowledge as an essential asset for sustainable development, based on an extensive examination of academic literature. Thus this research examines the impact of integrating these traditions within education, aimed at addressing environmental and socio-economic concerns while fostering appreciation for cultural heritage which guarantees a comprehensive and inclusive route to attaining global sustainability objectives.